The Adjustment of Boys from Boys Town South Africa’s Programmes within the First Year after Disengagement. - Miller, Barbara (My University, 2006)
This study investigated the adjustment of twenty boys a year after they had been disengaged from Boys Town (SA). An exploratory descriptive design was used. Two questionnaires were administered, one to the twenty boys and the other to their caregivers. Biographical details were obtained from the Proposed Disengagement forms completed by the Children’s homes six months prior to disengagement. Sixty boys were disengaged at the end of 2002. All were targeted to take part. The results showed that fifty percent of the boys were able to make a satisfactory adjustment. Twenty five percent made an unsatisfactory adjustment and twenty five percent a neither satisfactory nor unsatisfactory adjustment. Stability in terms of accommodation, school performance, work stability, family relationships, peer relations, social adjustment and generalized contentment formed the criteria against which the adjustment was measured. The use made by the boys and their caregivers of reconstruction and aftercare services as well as the sustainability of the changes that had occurred at Boys Town were examined. Recommendations include the development of a specialized aftercare programme to address the major problems highlighted by the research. Problems were identified in the areas of accommodation, substance abuse, dropping out of school or college and difficulties with finding work. The need for counseling particularly family therapy and work between sons and their fathers, stepfathers and foster fathers was highlighted.
Master of Arts in Social Work - Social Work
Keywords: boys; adjustment; south africa; boys town; disengagement